2014
DOI: 10.1115/1.4028583
|View full text |Cite
|
Sign up to set email alerts
|

Numerical Study of Turbulent Flow and Convective Heat Transfer Characteristics in Helical Rectangular Ducts

Abstract: Three-dimensional turbulent forced convective heat transfer and its flow characteristics in helical rectangular ducts are simulated using SST k-x turbulence model. The velocity field and temperature field at different axial locations along the axial direction are analyzed for different inlet Reynolds numbers, different curvatures, and torsions. The causes of heat transfer differences between the inner and outer wall of the helical rectangular ducts are discussed as well as the differences between helical and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
1
2
0
Order By: Relevance
“…Among these three, helical type GHE was reported to perform best albeit with higher installation cost [4]. This finding is consistent with past studies that reported higher heat transfer rates in helical channels compared to that of straight ones due to the induction of turbulent flow within the pipe [5]. With respect to the circulating heat transfer medium, ground source heat pumps that employ GHEs can be classified as regular geothermal heating/cooling systems or direct expansion-ground coupled heat 1094 (2022) 012008 IOP Publishing doi:10.1088/1755-1315/1094/1/012008 2 pumps (DX-GCHP).…”
Section: Introductionsupporting
confidence: 88%
“…Among these three, helical type GHE was reported to perform best albeit with higher installation cost [4]. This finding is consistent with past studies that reported higher heat transfer rates in helical channels compared to that of straight ones due to the induction of turbulent flow within the pipe [5]. With respect to the circulating heat transfer medium, ground source heat pumps that employ GHEs can be classified as regular geothermal heating/cooling systems or direct expansion-ground coupled heat 1094 (2022) 012008 IOP Publishing doi:10.1088/1755-1315/1094/1/012008 2 pumps (DX-GCHP).…”
Section: Introductionsupporting
confidence: 88%
“…From the results of numerical simulation, we found that the cyclic thermal action had differences on the distribution of indoor temperature field for different roof structures. At the same time, the roles of roof forms applicable to farm buildings on different temperate zones in summer thermal insulation were also different 31 .…”
Section: Resultsmentioning
confidence: 99%
“…Among the various passive methods, one promising method is the application of coiled tubes. For decades, coiled tubes have been a major focus in heat transfer engineering due to its high heat transfer rate and compactness [1][2][3]. Their unique characteristics have attracted considerable attention from researchers worldwide.…”
Section: Introductionmentioning
confidence: 99%